Wewenang Perawat Dalam Meningkatkan Indeks Pembangunan Kesehatan Masyarakat di Kabupaten Garut Dihubungkan Dengan UU Keperawatan No 38 Tahun 2014 - Gin Gin Sugih Permana (Jurnal Medika Cendikia, 2016)
The Human Development Index (HDI) problems, which is influenced by Public Health Development Index or IPKM of Garut District is still a major concern, particularly by the Government of Garut District. A lot of attempts have been made to improve the health development more effective and efficient as well as closer to the community health, improve the distribution and quality of service, especially for secluded areas, continuously and simultaneously to improve the quality of human resources. Through the implementation of Act No. 38/2014 about Nursing, health development within the optimization of the role of nurses is expected to be more intensive, sustainable and evenly distributed and supported by more steady of health information, in order to increase the public health degree. This research aimed to describe the role of nurses in improving the Public Health Development Index of Garut District currently associated with the implementation of Act No. 38/2014 about Nursing. The role of the nurse is as directly care givers, educators, health inspectors, consultants, collaborators, facilitators, inventor of the case, and modifier of the environment in order to increase the life expectancy (AHH), maternal mortality (AKI), and infant mortality rate (AKB) as expected. The research uses a qualitative method through inductive-descriptive approach to explain the phenomena occured, the relationship and influence between or against ones to the other phenomenon. The data analysis techniques used are credibility, transferability, dependability, and confirmability to obtain more objective data with a high degree of validity. The results found and concluded, associated with increased IPKM, nurses has a very important role very clearly. Although still lacking in terms of quantity, but its role is strongly felt, especially when a doctor or medical personnel and other technical experts are not placed, but in field work or task being outside. It looked from the IPKM of Garut District is 69.76 points which is still below the target of 72.25 points. The conditions allows the nurse to have an authority held by the Independent Nursing Practice with fulfillment of certain criteria, so that they role to improve IPKM direct or indirectly, including provide or promote the importance of health to the public in order to maintain the their health and environment independently. Although some facts also show that nurses have not been able to fully play the role in providing health education to the public and family.